IMPLEMENTATION OF THE SAME DAY SERVICE PROGRAMIN REALIZING THE LEVEL OF SERVICE QUALITY (TMP) PT. PLN (PERSERO) PADANG PANJANG CUSTOMER SERVICE UNIT - Hendro Satria; Hasim As’ari (ADISAM PUBLISHER, 2022)
The increasing demand for electricity by customers caused by various factors such as WFH (work from home), the development of technology that requires electrical energy as its driving force and the increasing population growth rate makes PT. PLN as the main electricity provider need a solution to answer these problems by implementing a program same day service. PT. PLN (Persero) ULP Padang Panjang is the smallest service unit of PT. PLN (Persero) which organizes the Same Day Service program. The Same Day Service program is presented to cut service time to be more effective. The purpose of this research was to determine and analyze the Implementation of the Same Day Service Program and its inhibiting factors. This research used the theory of policy implementation proposed by George C. Edward III which consists of communication, resources, disposition and bureaucratic structure. The research method used is qualitative with data collection techniques through observation, interviews and documentation. The results of this research indicate that the implementation of the Same Day Service Program at PT. PLN (Persero) ULP Padang Panjang has not run optimally. The inhibiting factors for the Same Day Service Program are the lack of socialization of the implementor to the program targets, the lack of human and financial resources and the mechanism set out in the Standard Operating Procedure (SOP) which does not pay attention to the inhibiting aspects in the program implementation process.